Double mucocele of the paranasal sinuses. - Weissman, J L; Curtin, H D; Eibling, D E (American Journal of Neuroradiology, 1994)
We have observed two contiguous mucoceles in one patient. Based on the mucoceles’ signal intensities on MR imaging, as well as their anatomic location as delineated by CT and MR, we hypothesize that the "downstream" mucocele obstructed the "upstream" sinus, leading to formation of a secondary mucocele.